Phase III development of the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire module for women undergoing breast reconstruction. Issue 4 (29th January 2014) - Winters, Z. E.; Balta, V.; Thomson, H. J.; Brandberg, Y.; Oberguggenberger, A.; Sinove, Y.; Unukovych, D.; Nava, M.; Sandelin, K.; Johansson, H.; Dobbeleir, J.; Blondeel, P.; et al.
<x xml:space="preserve">Abstract</x> Background Comprehensive outcome assessments after breast reconstruction (BRR) require surgery‐specific patient‐reported outcome measures. The aims of this study were to assess the relevance, acceptability and redundancy of questions/items (phase III pretesting) of a new BRR questionnaire evaluating patients' health‐related quality of life before and after BRR. Phase III occurred in collaboration with the European Organization for Research and Treatment of Cancer (EORTC) following earlier development phases that identified 31 items. Methods The EORTC BRR subgroup applied decision‐making rules to each question according to eight EORTC criteria. A total of 197 patients (from the UK, Austria, Belgium, Italy and Sweden) were recruited. Forty‐seven patients completed pre‐ and post‐BRR questionnaires prospectively, and 150 reported post‐BRR questionnaires only retrospectively. Qualitative debriefing interviews were undertaken in 189 patients. Preliminary psychometric analyses were performed. Results Thirty‐one items fulfilled 'relevance', with none producing 'difficulties'. Ten items were not a priority for 10 per cent of respondents. Of these, two questions concerning muscle twitching in the affected breast and problem with donor‐site swelling were deleted. Three redundant items were deleted: weakness in arm, which correlated significantly to the Quality of Life Questionnaire (QLQ) BR23 breast questionnaire, and shape and colour of the affected nipple. Descriptive statistics reduced the module to 26 items conceptualized into three provisional scales (disease treatment/surgery‐related symptoms, sexuality and cosmetic outcome) within the newly completed questionnaire, EORTC QLQ‐BRR26. Conclusion The QLQ‐BRR26 is available for psychometric validation in a large‐field international sample. The intended use for QLQ‐BRR26 is alongside EORTC QLQ‐C30 and QLQ‐BR23, in women treated by mastectomy for breast cancer and undergoing all types of BRR.